2000
DOI: 10.1002/1099-159x(200009/10)8:5<503::aid-pip347>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

HITTM cells?high-efficiency crystalline Si cells with novel structure

Abstract: Our unique, high‐efficiency c‐Si solar cell, named the HIT cell, has shown considerable potential to improve junction properties and surface passivation since it was first developed. The improved properties in efficiency and temperature dependence compared to conventional p – n diffused c‐Si solar cells are featured in HIT power 21TM solar cell modules and other applications which are now on the market. In the area of research, further improvement in the junction properties of the a‐Si/c‐Si heterojunction has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
185
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(189 citation statements)
references
References 7 publications
0
185
0
2
Order By: Relevance
“…Several innovations in solar cell design Figure 8. Typical I-V curve for a GaN/InGaN solar cell with semi-transparent p-contact metal make this possible, including the move to thinner silicon junctions, the passivation of Si surfaces by means other than insulators, 16 the use of an optically transparent substrate and recently demonstrated high minority carrier lifetimes in n-type silicon. Silicon solar cells were fabricated using the deposition of the wide-band gap semiconductor, amorphous silicon to passivate the surfaces, and achieve higher voltages and efficiencies.…”
Section: Silicon Solar Cell Filtered By Gaasmentioning
confidence: 99%
“…Several innovations in solar cell design Figure 8. Typical I-V curve for a GaN/InGaN solar cell with semi-transparent p-contact metal make this possible, including the move to thinner silicon junctions, the passivation of Si surfaces by means other than insulators, 16 the use of an optically transparent substrate and recently demonstrated high minority carrier lifetimes in n-type silicon. Silicon solar cells were fabricated using the deposition of the wide-band gap semiconductor, amorphous silicon to passivate the surfaces, and achieve higher voltages and efficiencies.…”
Section: Silicon Solar Cell Filtered By Gaasmentioning
confidence: 99%
“…[1][2][3][4] One of the key points in the device performance is the incorporation of thin intrinsic hydrogenated amorphous silicon (a-Si:H) layers on both sides of the crystalline silicon (c-Si) substrate. It has been shown that the quality of these layers affects the external parameters of the device, [5][6][7] therefore, the fabrication process and the properties of the a-Si:H layers have a great impact on the efficiency of the SHJ solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon heterojunction solar cells have a high conversion efficiency potential, [1][2][3][4][5] up to 23% to date. 6 The passivation of the crystalline silicon ͑c-Si͒ wafer surfaces is usually performed by very thin intrinsic amorphous silicon ͑a-Si:H͒ layers, deposited by rf plasma-enhanced chemical vapor deposition ͑PECVD͒ ͑Refs.…”
mentioning
confidence: 99%